Peran BAZNAS Kabupaten Purbalingga Dalam Mengurangi Kemiskinan Perspektif Sustainable Development Goals (Goal 1: No Poverty) - Bagas Novi Ardhani; Maruf Hidayat (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to analyze the implementation of BAZNAS Purbalingga programs and assess their relevance to the indicators of SDG Goal 1. This research uses a qualitative descriptive method. The results show that program implementation involves application, assessment, approval, disbursement, and evaluation, though challenges remain, such as mustahik dependency and limited data. From the SDGs perspective, BAZNAS contributes through consumptive programs (basic needs, health) and productive programs (business capital), which align with several Goal 1 indicators. However, its role is not yet optimal, requiring strategy reinforcement and stronger cross-sectoral synergy.